Lymphocyte antigen 6 superfamily member D is a marker of urothelial and squamous differentiation: implications for risk stratification of bladder cancer - Nina Andersson; Johan Ohlsson; Sara Wahlin; Björn Nodin; Karolina Boman; Sebastian Lundgren; Karin Jirström (BMC, 2020)
Abstract Background Screening across a multitude of normal and malignant tissues revealed an enhanced expression of lymphocyte antigen 6 superfamily member D (LY6D) in squamous epithelium and urothelium, as well as in malignancies derived therefrom. The aim of this study was to further delineate the protein expression of LY6D in urothelial bladder cancer, with particular attention to its relationship with clinicopathological characteristics and patient outcome. Methods Immunohistochemical expression of LY6D was assessed in tissue microarrays with urothelial bladder cancer tumours from three independent patient cohorts; one with transurethral resection of the bladder (TURB) specimens of mixed tumour stages from 110 consecutive cases, one with tumours of mixed stages from 260 incident cases in a population-based cohort, and one with paired TURB specimens, resected tumours and a subset of lymph node metastases from 145 patients with muscle-invasive bladder cancer (MIBC). Chi-square and non-parametric tests were applied to examine associations of LY6D expression with clinicopathological characteristics. Kaplan-Meier and Cox regression analyses were applied to examine 5-year overall survival (OS) and recurrence free survival (RFS) in relation to LY6D expression. Results In the two cohorts with mixed stages, positive LY6D expression was denoted in 63 and 64% of the cases, respectively, and found to be significantly higher in low-grade and less invasive tumours. Negative LY6D expression was significantly associated with a reduced 5-year OS, although not independently of established prognostic factors. In the population-based cohort, LY6D expression was higher in tumours with squamous differentiation and lower in other variant histologies compared to pure urothelial tumours, and the association of LY6D expression with survival was somewhat enhanced after exclusion of the former. LY6D expression was generally lower in the MIBC cohort, and even more reduced in resected tumours compared to TURB specimens in patients who had not received neoadjuvant chemotherapy. There were no significant associations between LY6D expression and RFS, neither allover nor in relation to neoadjuvant chemotherapy. Conclusion LY6D is a marker of urothelial and squamous differentiation that may add useful diagnostic and prognostic information to better guide the clinical management of bladder cancer, given that the presence of variant histology is taken into account.